Changes in Self- and Informant-Reported Frontal Behaviors in Parkinson's Disease: A Longitudinal Study. (January 2022) - Pluim, Celina F.; Nakhla, Marina Z.; Split, Molly; Filoteo, J. Vincent; Litvan, Irene; Moore, Raeanne C.; Lessig, Stephanie; Schiehser, Dawn M.
Objective: Frontal behaviors (i.e., executive dysfunction, disinhibition, apathy) are common in Parkinson's disease (PD). However, it is unclear if patient and informant reports of patient frontal behaviors are in agreement over time. Method: Sixty-two PD patients without dementia and their informants (87% spouses/partners) completed the self- and informant-versions of the Frontal Systems Behavior Scale at baseline and 2-year follow-up. Dyad ratings were compared and predictors of behavior ratings were examined. Results: Patient and informant reports at baseline and follow-up were in agreement, with significant increases in overall frontal behaviors, executive dysfunction, and apathy. Higher levels of baseline patient depression and caregiver burden predicted decrements in patient-reported executive function; worse patient cognition at baseline predicted worsening apathy as rated by informants. Conclusions: PD patients and their informants are concordant in their ratings of worsening frontal behaviors over time. Targeting patient depression, cognition, and caregiver burden may improve decrements in frontal behaviors (executive dysfunction and apathy) in PD.